Neuro-economics and Strategic Decisions: The Impact on Financial Sustainability of Multinational Enterprises - Asuquo - Utuk, Kokoete (Universidad Francisco de Paula Santander, 2023)
More than ever, engaging a multidisciplinary approach in decision-making displays an arsenal of capacity necessary for success across managerial concerns in all sectors of the economy. Psychology and economics capturing human behaviors form part of this interdisciplinary research that spans the years though many are far from this reality. The paper shows the impact of neuro-economics on strategic financial decisions in multinational enterprises deploying theories of decisions, utility, and expectations across MNCsin the media industry in Nigeria while addressing the effects of emotions affecting advertising outcomes and branding, and financial decisions building the theoretical framework from resources from Google Scholar and Scopus search engines. Utilizing five MNCs as a sample in a population of 15 registered media firms in Nigeria, the study uses grounded theory methodology and focus group discussions to uncover the reality of emotional influence on strategic decisions and multiple regression analysis to test for the statistical significance of independent variables on the dependent variable. The output shows that neuro-economics contributes significantly to all economic decision-making in all sectors, including the media industry.Although research generalization is challenging due to economic variations in different markets, the report posts resourceful information for policy-making decisions, productivity, and wealth creation.